Assessing soil temperature and moisture fluctuations under irrigated banana (Musa spp.) cultivation in response to coconut coir mulch cover - Renato Augusto Soares Rodrigues; João Luis Mendes Pedroso de Lima; Abelardo Antônio Assunção Montenegro; Thayná Almeida; José Roberto Lopes da Silva (Dyna, 2023)
The semiarid is characterized by extreme heat, which affects agricultural production by limiting the soil's ability to retain water. The objective of this study was to investigate the influence of mulch on soil temperature and soil moisture in a drip irrigated banana plantation in a Brazilian semiarid region. Six thermocouples and three soil moisture probes were used, with coconut coir as mulch. Daytime and nighttime surface temperatures were compared for two mulch densities (4 and 8 t ha-1) and bare soil. Soil temperature and moisture were measured at three depths (0.1, 0.3 and 0.5 m). The study was conducted from November 2014 to March 2015. Mulch had a buffer effect on soil temperature fluctuation. Drip irrigation management associated with mulch provided a uniform moisture profile close to field capacity.